THD analysis and small AC signal analysis of trans-Z-source and quasi-Z-source inverter for linear and non-linear load - Bharat, Manish; Murty, ASR; Dash, Ritesh (Institute of Advanced Engineering and Science, 2023)
The paper primarily focuses on the ongoing research related to Z source inverter technologies (ZSITs) used in the transportation industry, particularly for electric vehicles (EVs) and hybrid electrical vehicles (HEVs). It analyzes various topologies of ZSITs based on their mode of operation, capacitor voltage stress during active states and non-active state operations, DC link voltage before inverter module and line to line output voltage across the load. The paper compares the conventional trans-z source and two port quasi-Z source inverter model networks for multiple parameters and derives mathematical equations for both linear and non-linear loads. Practical and theoretical calculations match when using a modulation index of M=0.85 and a duty ratio of 1.414. The result obtained in this paper indicates that the proposed solution is better in terms of reduction in total total harmonics distortions (THD) percentage of 18.14% during the transition condition. All the analysis has been carried out with MATLAB based Simulink model.